Nigerian dental students' permissive tendency to the proposed organized incorporation of stem cells application into dental curriculum: A cross-sectional study - Matthew A Sede; Ochuwa Audu; Clement Chinedu Azodo (Wolters Kluwer Medknow Publications, 2016)
Aim: This study aims to examine the Nigerian dental students' permissive tendency to the proposed organized incorporation of stem cells application into undergraduate and postgraduate dental curriculum. Materials and Methods: This cross-sectional study of Nigerian final year dental students was conducted between April and June 2014 using the modified Sede et al. questionnaire on stem cell use in dentistry knowledge and attitude questionnaire as the data collection tool. Results: Of the 110 participants, 63.6% reported awareness of stem cell use in dentistry with their leading information sources as school lecture and internet. Subjective and objective stem cell knowledge assessment revealed inadequate knowledge among the majority of the participants. Subjective knowledge emerged as the significant determinant of objective stem cell knowledge. About a third (32.7%) of the participants reported a positive attitude toward stem cell application and objective stem cell knowledge was the only significant determinant of attitude. The majority (82.7%) of the participants reported a positive permissive tendency to the proposed organized incorporation of stem cells application into undergraduate, and postgraduate dental curriculum and attitude toward stem cell emerged as the only significant determinant. Conclusion: High positive permissive tendency to the proposed organized incorporation of stem cell application into undergraduate and postgraduate dental curriculum was noted among the participants. Increasing stem cell knowledge will improve attitude toward stem cell use which will ultimately increase positive permissive tendency.